2002
DOI: 10.3168/jds.s0022-0302(02)74151-9
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Degradation and Availability of Various Amounts of Liquid Methionine Hydroxy Analog in Lactating Dairy Cows

Abstract: Ruminal escape of various amounts of methionine hydroxy analog [D,L-2-hydroxy-4-(methylthio)-butanoic acid (HMB)] was measured in an experiment designed as a 4 x 4 Latin square using four lactating dairy cows with cannula in the rumen and duodenum. The cows were fed a diet composed of corn silage, alfalfa haylage, rolled barley grain, canola meal, and blood meal, three times per day. The cows were fed the liquid analog each day for 1 wk before the experiment was started. On the day of the experiment, each cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 28 publications
6
49
1
1
Order By: Relevance
“…Actually, HMB did not totally escape rumen microbial metabolism and could be a source of Met for rumen microorganisms. Previous studies indicated 40‐50% ruminal escape of HMB (Vázquez‐Añón et al ; Koenig et al ), which showed a significant amount of HMB was metabolized in the rumen. Because of the ruminal degradability, HMB could affect microbial fermentation by a direct stimulatory effect of Met on certain cellulolytic bacteria or through an indirect effect on the noncellulolytic species in the rumen (Martin et al ).…”
Section: Discussionmentioning
confidence: 91%
“…Actually, HMB did not totally escape rumen microbial metabolism and could be a source of Met for rumen microorganisms. Previous studies indicated 40‐50% ruminal escape of HMB (Vázquez‐Añón et al ; Koenig et al ), which showed a significant amount of HMB was metabolized in the rumen. Because of the ruminal degradability, HMB could affect microbial fermentation by a direct stimulatory effect of Met on certain cellulolytic bacteria or through an indirect effect on the noncellulolytic species in the rumen (Martin et al ).…”
Section: Discussionmentioning
confidence: 91%
“…On average, cows infused with dl-Met were provided with lower levels of Met; however, as this was assumed to be 100% absorbed, MP Met differences were comparable for dl-Met, Mepron, and Smartamine. Cows fed HMTBa were fed a higher amount of supplemental Met equivalent than cows fed the other sources; however, due to degradation of the product within the rumen (assuming 40% of HMTBa escaped rumen degradation; Koenig et al, 1999Koenig et al, , 2002Vázquez-Añón et al, 2001), predicted MP Met was not changed as much in HMTBa-fed cows.…”
Section: Database Descriptionmentioning
confidence: 90%
“…Also missing from previous analyses are experiments that evaluated the use of HMTBa as a source of supplemental MP Met. Whereas the rumen escape of HMTBa has been debated in the literature (Koenig et al, 2002;Noftsger et al, 2005;Zanton et al, 2012), the production effects of HMTBa have been extensively investigated. However, a comprehensive estimate of the effectiveness of supplementation is unavailable for lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Limited data have suggested a possible effect of HM-TBa on rumen fermentation, fiber degradability, and microbial protein synthesis. With a reported ruminal degradability of 50% or more (Koenig et al, 1999(Koenig et al, , 2002Noftsger et al, 2005), HMTBa could affect microbial fermentation by a direct stimulatory effect of Met on certain cellulolytic bacteria or through an indirect effect on the noncellulolytic species in the rumen (Martin et al, 2013). Vazquez-Añon et al (2001) reported, for example, a quadratic increase in bacterial N outflow and the efficiency of bacterial N synthesis in continuous culture fermenters.…”
Section: Introductionmentioning
confidence: 99%